2015
DOI: 10.1093/jac/dkv198
|View full text |Cite
|
Sign up to set email alerts
|

Invasive mould sinusitis in patients with haematological malignancies: a 10 year single-centre study

Abstract: Despite combined medical and surgical therapy, IMS had high mortality. Mortality risk factors were relapsed and/or refractory malignancy, cytopenia and Aspergillus infection in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 41 publications
3
56
0
Order By: Relevance
“…Similar to our results, Davoudi et al observed that hematologic malignancy is associated with increased risk of death at 3 months . In accordance with previous studies, diabetes correlated with improved survival on univariate analysis .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Similar to our results, Davoudi et al observed that hematologic malignancy is associated with increased risk of death at 3 months . In accordance with previous studies, diabetes correlated with improved survival on univariate analysis .…”
Section: Discussionsupporting
confidence: 93%
“…Acute invasive fungal sinusitis (AIFS) is a rare infection that typically occurs in immunocompromised patients when fungi, usually Aspergillus or Mucor , invade the mucosa of the paranasal sinuses and destroy adjacent structures through angioinvasion . Its mortality is high even with timely diagnosis and treatment: ∽50% in the largest meta‐analysis to date .…”
mentioning
confidence: 99%
See 3 more Smart Citations